2014
DOI: 10.1016/j.bmcl.2014.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity of carbamate derivatives of melampomagnolide B

Abstract: Melampomagnolide B (MMB) is a natural sesquiterpene structurally related to parthenolide (PTL). We have shown that MMB exhibits anti-leukemic properties similar to PTL. Unlike PTL, the presence of a primary hydroxyl group in the MMB molecule allows the opportunity for examining the biological activity of a variety of conjugated analogs of MMB. We have now synthesized a series of carbamate analogs of MMB and evaluated these derivatives for anti-cancer activity against a panel of sixty human cancer cell lines. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Initially, we investigated the synthesis of the C-14 imidazole and benzimidazole carbamate derivatives of MMB utilizing the p- nitrophenylchloroformate ester intermediate of MMB. 22 However, this conjugation procedure suffered from the drawback of low yields of the desired carbamate products and the production of unwanted C-13 Michael addition byproducts (5–10%). Also, although the p- nitrophenylchloroformate ester intermediate worked satisfactorily for strongly nucleophilic amines, it did not prove to be useful for poorly nucleophilic aromatic amines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, we investigated the synthesis of the C-14 imidazole and benzimidazole carbamate derivatives of MMB utilizing the p- nitrophenylchloroformate ester intermediate of MMB. 22 However, this conjugation procedure suffered from the drawback of low yields of the desired carbamate products and the production of unwanted C-13 Michael addition byproducts (5–10%). Also, although the p- nitrophenylchloroformate ester intermediate worked satisfactorily for strongly nucleophilic amines, it did not prove to be useful for poorly nucleophilic aromatic amines.…”
Section: Resultsmentioning
confidence: 99%
“…21 MMB is somewhat less potent than PTL, but both sesquiterpenes exhibit significantly reduced cytotoxicity against normal bone marrow stem cells when compared to their effect on AML stem cells. 21, 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 We have previously reported on the synthesis of a series of carbamate esters of MMB ( E , Fig. 1), that are potent cytotoxic agents against both hematological and solid tumor cancer cells lines, 16 and have also shown that dimeric carbamate and carbonate ester analogs of MMB ( F and G , Fig. 1) exhibit nanomolar cytotoxicity against a wide range of human cancer cells.…”
Section: Introductionmentioning
confidence: 98%
“…18,19 More recently, the Crooks lab generated a series of parthenolide and melampomagnolide-B analogues and screened them against a panel of 60 human cancer cell lines. 2022 The α-methylene-γ- butyrolactone functionality was appended to small molecules to covalently link them to their biological target. 23,24 These compounds with α-methylene-γ-butyrolactone also show anticancer activities.…”
Section: Introductionmentioning
confidence: 99%